Bioactive Properties, Fatty Acid Composition and Mineral Contents of Grape Seed and Oils - Al Juhaimi, F.; Geçgel, Ãœ; Gülcü, M.; Hamurcu, M.; Özcan, M.M. (South African Journal of Enology and Viticulture, 2017)
The oil content of grape seed samples changed between 4.53% (Adakarası) and 11.13% (Sauvignon blanc). While the linoleic acid contents of grape seed oils ranged from 47.34% (Sangiovese) to 72.91% (Cinsaut), the oleic acid contents varied between 13.35% (Cabernet Sauvignon) and 26.30% (Sangiovese) (p < 0.05). Also, the palmitic acid and stearic acid contents of grape seed oils ranged from 7.15% (Cinsaut) to 16.06% (Sangiovese) and from 2.43% (Narince) to 6.55% (Sangiovese) respectively (p < 0.05). The flavonoid contents of the seeds changed between 263.53 (mg CE/g) and 1 706.00 (mg CE/g) (Cabernet Sauvignon). Total phenols were found to be between 6 711.14 (mg GA/g extract) (Sangiovese) and 8 818.69 (mg GA/g extract) (Narince). The linoleic contents of oils changed from between 47.34% (Sangiovese) and 72.91% (Cinsaut). The K contents of the grape seed samples changed between 4 347.80 mg/kg (Cabernet Sauvignon) and 9 492.60 mg/kg (Gamay) (p < 0.05). The Fe contents of seeds were found to be between 29.96 mg/kg (Narince) and 73.82 mg/kg (Sangiovese). As a result, the current study shows that grape seeds are useful for human nutrition due to their components.